2009
DOI: 10.1161/atvbaha.108.183038
|View full text |Cite
|
Sign up to set email alerts
|

The Capacity of Group V sPLA 2 to Increase Atherogenicity of ApoE −/− and LDLR −/− Mouse LDL In Vitro Predicts its Atherogenic Role In Vivo

Abstract: Objective-In vitro data indicate that human LDL modified by Group V secretory phospholipase A 2 (GV sPLA 2 ) is proatherogenic. Consistent with this, gain and loss of function studies demonstrated that GV sPLA 2 promotes atherosclerosis in LDLR Ϫ/Ϫ mice. The current study investigates whether GV sPLA 2 promotes atherosclerotic processes in apoE Ϫ/Ϫ mice. Methods and Results-LDL (dϭ1.019 to 1.063) from apoE Ϫ/Ϫ and LDLR Ϫ/Ϫ mice fed chow or Western diet were hydrolyzed by GV sPLA 2 . Phosphatidylcholine on LDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 35 publications
(39 reference statements)
2
23
1
Order By: Relevance
“…However, the reduction in lesion area was not seen in apoE Ϫ/Ϫ mice lacking sPLA 2 -V, despite reduced collagen deposition in these mice. 84 In these studies, sPLA 2 -V did not alter foam cell formation in response to LDL from apoE Ϫ/Ϫ mice, whereas hydrolysis of LDL from LDLr Ϫ/Ϫ mice was a prerequisite for this process. These results suggest that the proatherogenic properties of sPLA 2 -V may depend in large part on its ability to enhance the proatherogenic potential of LDL.…”
Section: -V In Ldlrmentioning
confidence: 67%
See 1 more Smart Citation
“…However, the reduction in lesion area was not seen in apoE Ϫ/Ϫ mice lacking sPLA 2 -V, despite reduced collagen deposition in these mice. 84 In these studies, sPLA 2 -V did not alter foam cell formation in response to LDL from apoE Ϫ/Ϫ mice, whereas hydrolysis of LDL from LDLr Ϫ/Ϫ mice was a prerequisite for this process. These results suggest that the proatherogenic properties of sPLA 2 -V may depend in large part on its ability to enhance the proatherogenic potential of LDL.…”
Section: -V In Ldlrmentioning
confidence: 67%
“…These results suggest that the proatherogenic properties of sPLA 2 -V may depend in large part on its ability to enhance the proatherogenic potential of LDL. 84 Although sPLA 2 -X is the most efficient sPLA 2 to hydrolyze LDL and high-density lipoproteins 51 and to promote foam cell formation, 57 no direct evidence for a role of this isoform in atherosclerosis is currently available.…”
Section: -V In Ldlrmentioning
confidence: 99%
“…We have had a long-standing interest in the sPLA2 enzymes 26,27 because they were identified as potential risk markers for CHD both from animal studies [10][11][12] and observational analyses. The aim of the present study was to investigate the contribution of sPLA2-X to the complex measure of sPLA2 activity, a marker of CHD risk, 28 by examining the association of PLA2G10 variants with sPLA2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…12 Thus, by extrapolation, sPLA2-X, as the most potent of the 3 sPLA2s in hydrolyzing the most abundant phospholipid phosphotidylcholine, 13 could also be considered to be proatherogenic, and indeed it has been shown that PLA2G10 enhances foam cell formation in vitro by promoting atherogenic low-density lipoprotein (LDL) formation. 14 Transgenic mice overexpressing Pla2g10 have been shown to die neonatally because of severe lung pathology, suggesting a role for sPLA2-X overexpression in inflammatory airway diseases.…”
mentioning
confidence: 99%
“…Human low density lipoprotein modified by GV sPLA 2 is pro-atherogenic and promotes macrophage foam cell formation and overexpression of GV sPLA 2 increases, and targeted deletion of GV sPLA 2 decreases atherosclerotic plaque size in low density lipoprotein receptor-deficient mice (51,52). Based on these observations, pharmacologic inhibition of GV sPLA 2 has been identified as a possible therapeutic strategy for patients with atherosclerosis (21,53).…”
Section: Discussionmentioning
confidence: 99%